2014
DOI: 10.4254/wjh.v6.i7.532
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein thrombosis with protein C-S deficiency in a non-cirrhotic patient

Abstract: There are several conditions that can lead to portal vein thrombosis (PVT), including including infection, malignancies, and coagulation disorders. Anew condition of interest is protein C and S deficiencies, associated with hypercoagulation and recurrent venous thromboembolism. We report the case of a non-cirrhotic 63-year-old male diagnosed with acute superior mesenteric vein thrombosis and PVT and combined deficiencies in proteins C and S, recanalized by short-term low molecular heparin plus oral warfarin th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In Mexico, Majluf-cruz et al studied 36 patients with portal hypertension and non-cirrhotic portal vein thrombosis. They found that 30% of the patients had protein C deficiency and 9% had protein S deficiency [9].…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, Majluf-cruz et al studied 36 patients with portal hypertension and non-cirrhotic portal vein thrombosis. They found that 30% of the patients had protein C deficiency and 9% had protein S deficiency [9].…”
Section: Discussionmentioning
confidence: 99%
“…Various causes and predisposing factors of venous thrombosis have been reported in literature. 3,8 The diagnosis of inherent protein-C and protein-S deficiency is very crucial and most of the patients present with other predisposing factors too. In the present case, the clinical, radiological, and laboratory evaluations and all the unusual sites of thrombosis guided the physician towards the diagnosis of protein-C and protein-S deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is also frequent in the hypercoagulability settings such as malignancy and myeloproliferative disorders, etc. Portal vein thrombosis may present as an acute or chronic state.…”
Section: Diagnosis: Portal Vein Thrombosismentioning
confidence: 99%